Kinerja Pengelolaan Keuangan Pemerintahan Kota Surabaya - Selya Budi Juliana; Septiana Dinda Aulia; Indah Ayu Oktavia; Maulidia Mawanti; Sifa Cahya Maula; Fandi Prasetya (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
This research was conducted with the aim of examining the financial management performance of the Surabaya City Regional Government. By using quantitative descriptive research methods. And using secondary data sources, namely the Surabaya City Budget Realization Report (LRA) 2018 - 2022. In analyzing the performance of researchers using the independence ratio, compatibility ratio, growth ratio, and effectiveness ratio. Based on the results of the study, it was found that the ratio of regional financial independence of the Surabaya City Government in 2018-2022 was categorized as high. However, the calculation of the compatibility ratio analysis of capital expenditure compared to operational expenditure shows that there is no compatibility. The ratio of regional financial growth of the Surabaya City government is also still in the low category. and for the effectiveness ratio of Regional Original Revenue (PAD) Surabaya City is still running quite effectively. However, this study still has limitations, namely in the use of data sources which are limited to financial statement data two years before the pandemic, during the pandemic, and two years after the pandemic. With these limitations, further research is expected to expand the observation period and discuss in more detail the financial performance of local governments using qualitative methods.